Chromosome 5q33 deletions associated with congenital heart defects. Issue 12 (2nd September 2016) - Starkovich, Molly; Lalani, Seema R.; Mercer, Catherine L.; Scott, Daryl A.
Abstract : Congenital heart defects (CHD) are present in over 1% of all newborns and are the leading cause of birth‐defect‐related deaths in the United States. We describe two male subjects with CHD, one with an atrial septal defect, a ventricular septal defect, and pulmonary artery stenosis; and the other with tetralogy of Fallot and a right aortic arch, who carry partially overlapping, de novo deletions of chromosome 5q33. The maximum region of overlap between these deletions encompasses HAND1 and SAP30L, two genes that have previously been shown to play a role in cardiac development. HAND1 encodes a basic helix‐loop‐helix transcription factor. Cardiac‐specific ablation of Hand1 in mice causes septal, valvular, and outflow tract defects. SAP30L, its paralog SAP30, and other SAP proteins form part of a multi‐subunit complex involved in transcriptional regulation via histone deacetylation. Morpholino knockdown of sap30L in zebrafish, which do not have a distinct sap30 gene, leads to cardiac hypoplasia and cardiac insufficiency. We subsequently identified two other individuals with chromosomal deletions involving HAND1 and SAP30L in whom cardiac‐related medical problems were not described. These observations suggest that haploinsufficiency of HAND1 and/or SAP30L may contribute to the development of CHD, although the contribution of other genes on chromosome 5q33 cannot be excluded. Our findings also suggest that the penetrance of CHD associated with 5q33 deletions is incomplete and may be influenced by other genetic, environmental or stochastic factors. © 2016 Wiley Periodicals, Inc.